Effects of gamma irradiation on macro and microelements of Boletus edulis Bull.: Fr. and Hydnum repandum L.: Fr. - Fernandes, Ângela (2015)
Mushrooms are considered excellent sources of minerals, being necessary to know the levels of essential elements in the edible species [1]. Mineral elements are classified in macro (e.g., Ca, Mg, Na, K) and microelements (e.g., Fe, Cu, Mn, Zn) with functions that include maintaining acid-base balance, osmotic regulation, oxygen transport and enzymatic cofactors [2-3]. Mushrooms need special caution in their conservation. Accordingly, treatments such as gamma rays have been applied to improve their shelf life and reduce health hazards caused by pathogenic microorganisms [4]. In this work, gamma irradiation was applied to Boletus edulis Bull.: Fr. and Hydnum repandum L.: Fr. to assess the effects on the minerals composition. The fruiting bodies were collected in Trás-os-Montes (Northeast of Portugal) in November 2012. Fresh samples were irradiated in experimental equipment with four 60Co sources, at 1 and 2 kGy. The studied mushrooms presented high levels of macro and microelements. Up to the applied doses, some significant differences were observed. However, in most cases, changes did not follow a marked tendency, being more likely to be derived from the natural variability in mineral accumulation as a result of mushroom growth in different ecosystems. Hence, irradiation treatment, using gamma rays up to 2 kGy, is a suitable technique to disinfest and/or decontaminate wild mushrooms, independently of their species or physical state.